Cell-to-cell and organ-to-organ crosstalk in the pathogenesis of alcohol-associated liver disease - Jing Ma; Suthat Liangpunsakul; Hui Gao; Nazmul Huda; Yanchao Jiang; Zhihong Yang; Ge Zeng; Themis Thoudam (eGastroenterology)
Alcohol-associated liver disease (ALD) is a growing global health concern and its prevalence and severity are increasing steadily. While bacterial endotoxin translocation into the portal circulation is a well-established key factor, recent evidence highlights the critical role of sterile inflammation, triggered by diverse stimuli, in alcohol-induced liver injury. This review provides a comprehensive analysis of the complex interactions within the hepatic microenvironment in ALD. It examines the contributions of both parenchymal cells, like hepatocytes, and non-parenchymal cells, such as hepatic stellate cells, Kupffer cells, neutrophils, and liver sinusoidal endothelial cells, in driving the progression of the disease. Additionally, we explored the involvement of key mediators, including cytokines, chemokines and inflammasomes, which regulate inflammatory responses and promote liver injury and fibrosis. A particular focus has been placed on extracellular vesicles (EVs) as essential mediators of intercellular communication both within and beyond the liver. These vesicles facilitate the transfer of signalling molecules, such as microRNAs and proteins, which modulate immune responses, fibrogenesis and lipid metabolism, thereby influencing disease progression. Moreover, we underscore the importance of organ-to-organ crosstalk, particularly in the gut-liver axis, where dysbiosis and increased intestinal permeability lead to microbial translocation, exacerbating hepatic inflammation. The adipose-liver axis is also highlighted, particularly the impact of adipokines and free fatty acids from adipose tissue on hepatic steatosis and inflammation in the context of alcohol consumption.